Effect of B-doping on the Crystal Structural and Optical Properties of Zinc Oxide Thin Films for Photonic Devices - Fery Adriyanto; Usman Santosa; Riyatun Riyatun; Wilson W. Wenas (Journal of Mathematical and Fundamental Sciences, 2001)
Abstract. Effect of B-doping B2H6 on the crystal structural and optical properties of zinc oxide (ZnO) thin films has been studied. The crystal orientation of these films were evaluated  by X-ray diffraction. It was found that the (110) reflection peak was dominant for all the film and became less pronounced as B2H6 flow rate was increased. The grain size of thin film decreased as B2H6 flow rate was increased. The transmittance in the ultraviolet  wavelengths region shifted to higher energy as the B2H6 flow rate was increased. I t was also found that refractive index of ZnO thin films increased as the B2H6 flow rate was further increased. These doping effects should be minimized  in order to grow low resistivity ZnO film with excellent optical properties for application to photonic devices. Efek Doping Boron (B) terhadap Struktur Kristal dan Sifat Optik Lapisan Tipis ZnO untuk Divais OptoelektronikSari. Telah dilakukan studi tentang pengaruh doping B2H6 terhadap struktur Kristal dan sifat optic lapisan tipis ZnO. Orientasi kristal lapisan tipisnya dievaluasi dengan difraksi sinar-x. Diperoleh bahwa puncak refleksi (110) mendominasi seluruh film dan berkurang sejalan dengan penambahan laju aliran B2H6. Ukuran butir Kristal dari film juga berkurang sejalan dengan penambahan laju aliran B2H6. Transmitnasi pada daerah panjang gelombang ultra violer bergeser ke arah energy yang lebih tinggi sejalan dengan penambahan laju aliran B2H6. Ditemukan pula bahwa indeks bias lapisan tipis ZnO bertambah sejalan dengan penambahan laju aliran B2H6. Efek-efek doping tersebut harus diminimalkan agar dapat diperoleh lapisan ZnO beresistivitas rendah dengan sifat optik yang baik untuk aplikasi pada divais fotonik.